About two left ventricular wounds - Cassinelli, Daniel; Larre Borges, Uruguay; Zagia, Miguel (Cirugía del Uruguay, 1971)
Two cases of cardiac wounds at the level of the left ventricle one of them caused by a blade and the other by a gun, were treated by surgery, with good evolution. The authors stress the fact that surgery was performed without removal of weapon (in the case of the blade), as well as the importance of diagnostic pericardiocentesis and the urgency and seriousness of ventricular wounds.